Potencialidade energética em extratores e tempos de extração do óleo de pinh̃o-manso (Jatropha curcas L.) em soxletter - Filho, André Luiz Melhorança; Pereira, Maria Renata Rocha [UNESP]; da Silva, José Iran Cardoso [UNESP] (My University, 2010)
The current rhythm of petroliferous exploration is esteem that the existing reserves will be depleted in next the 45 years. Thus being, it has that to study intensely, what it has come to be fact, the alternative power plants, as well as the technologies economically capable to ultilizar them. The potential demand of biodiesel for 2020 is taken in consideration that, in accordance with the International Agency of Energia (AIE), in only eight countries, will jump of 34,7 million tons in 2010 for 133,8 million in 2020, with an increment next to 300%. The tame nut is a producing oil plant with all the qualities necessary to be transformed into oil diesel. Beyond perennial and of easy culture, it presents good conservation of the harvested seed, being able to become great producer of substance cousin as optional fuel source. For these authors, this is a culture that can be developed in the small properties, with the available familiar man power, being plus a source of income for the country properties of the Northeast Region. The objective of this work is to evidence the capacity of oil production of the nut-bellwether, and the quality of extration with hexano and methanol in 6 distinct times.
Energy potentiality of the nut-bellwether (jatropha curcas l.) and different extractors and extraction times of the oil in soxletter
Keywords: Biodiesel; Hexano; Methanol; Nut-bellwether; Oil